Production innovations to enhance sweetpotato as a food security crop in northern Ghana - Sugri, I.; Akansake, D.A.; Abukari, I.A.; Low, Jan W.; Abidin, P.; Dery, E.K.; Acheremu, K.; Adjebeng‐Danquah, J.; Bidzakin, J.K.; Abubakari, M.; Lamini, S.; Carey, E.E. (Wiley, 2024)
Sweetpotato (Ipomoea batatas (L) Lam) is prioritized among crops that enhance food security and reduce malnutrition in Ghana. The production is expanding faster than other food crops owing to its superior nutrient composition. This study evaluates integrated approaches to increase on-farm productivity, income, and utilization of sweetpotato. The first part evaluated the agronomic yield performance, financial return, and sensory quality of 10 varieties under different fertilizer treatments. The second part of activities assessed both storage root and leaf composition (i.e., total sugars, dry matter, protein, Fe, Zn, Ca, total phenolic, total monomeric anthocyanins, lutein, zeaxanthin, α-tocopherol, β-carotene, and total carotenoids). Third, storage stability characteristics were assessed (i.e., shelf life and the incidence of decay). Application of NPK of 40:40:70 at 300 kg ha−1 significantly (p < 0.001) increased storage root yield from 12.4 to 17.3 t ha−1, which represents a 32% increase in yield compared to farmers’ standard practice. The variety SARI-JanLow (where SARI is Savanna Agricultural Research Institute) was outstanding for root yield (23.5 t ha−1) and β-carotene content (20.8 Mg 100 g−1). SARI-Tiemeh was consistently ranked among the three most preferred varieties by the sensory panel across the production hubs. At locations Nyankpala and Nikongo, the most responsive varieties to fertilizer application with regard to marketable storage root yield were SARI-Tiemeh (108%) and PGA14351-4 (79%), respectively. The varieties SARI-Nyumengre (1.4%), SARI-Nyoriberi-gu (1.4%), and PGA14351-4 (1.6%) were the least susceptible to sweetpotato weevil attack. Considering the benefit–cost ratio and a return on investments, the four most economically viable varieties appear to be SARI-JanLow, SARI-Suyolo, SARI-Tiemeh, and SARI-Nyoriberi-gu.